Using instructional scaffolding in a hybrid environment to Develop EFL Listening Comprehension skills among Primary Stage Pupils - دينا ايمن عبد الرحمن عبد البر; جيهان محمود رزق البسونى; محمود محمد محسب (Faculty of Education - Port Said University, 2023)
Using instructional scaffolding in a hybrid environment to Develop EFL Listening Comprehension skills among Primary Stage PupilsThe present study investigated the effectiveness of using instructional scaffolding in a hybrid learning environment to develop listening comprehension skills of primary stage pupils. This study adopted the quasi-experimental design as two intact groups of fifth grade primary stage pupils were chosen randomly; experimental and control groups. The participants were (60) pupils divided into two groups 30 pupils each. The experimental group received instruction through scaffolding strategy in a hybrid environment. Pupils were taught through face to face sessions and online sessions. The control group received regular instruction. A listening comprehension questionnaire and pre-post listening comprehension test were prepared and administered by the research for collecting data and validated by specialist jurors.. Results of the study proved the effectiveness of utilizing instructional scaffolding technique in a hybrid environment in developing EFL listening comprehension skills among primary stage pupils.